Slavemaster president the double career of James Polk - Dusinberre, William (Oxford Univ. Press, 2003)
James K. Polk held the office of President from 1845 to 1849, a period when the expansion of slavery into the territories emerged as a pressing question in American politics. During his presidency, the slave period of Texas was annexed and the future of slavery in the Mexican Cession was debated. Polk also owned a substantial cotton plantation in northern Mississippi and 54 slaves. He was an absentee master who had a string of overseers or agents manage his plantation and did not visit his estate while he was in the White House. In this book, William Dusinberre reconstructs the world of Polk's estate and the lives of his slaves, and analyzes how Polk's experience as a slavemaster conditioned his stance towards slavery-related issues. Dusinberre argues that Polk's policies helped precipitate the civil war he had sought to avert.